2014
DOI: 10.1016/j.jbusres.2013.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization's effect on marketing learning: A study of Syrian firms

Abstract: The aim of the present study is to understand the effects of international expansion on firms' acquisition of marketing learning. This study's focus on marketing learning complements previous research on the impact of internationalization on the development of foreign-market and technological knowledge. The research finds that the scope of a firm's international activities, perception of gaps in marketing knowledge, and external social capital positively influence firms' acquisition of marketing learning. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Firms will not be motivated to develop a formalized learning process when multinationality increases, if the majority of export decisions taken are for incrementally different markets. In summary, our study adds to previous exporting work (e.g., Hultman, Katsikeas, and Robson 2011; Ibeh and Kasem 2014) by observing and accounting for the fact that exporting firms domiciled in different strategic contexts have idiosyncratic experience profiles that generate differential learning processes and performance outcomes.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Firms will not be motivated to develop a formalized learning process when multinationality increases, if the majority of export decisions taken are for incrementally different markets. In summary, our study adds to previous exporting work (e.g., Hultman, Katsikeas, and Robson 2011; Ibeh and Kasem 2014) by observing and accounting for the fact that exporting firms domiciled in different strategic contexts have idiosyncratic experience profiles that generate differential learning processes and performance outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Peng 2001). As an organizational capability, processes of export learning capture the firm's exporting experiences and competencies, which enables the firm to coordinate exporting tasks by matching these knowledge resources with opportunities to stimulate demand growth (Ibeh and Kasem 2014;Souchon, Sy-Changco, and Dewsnap 2012).…”
Section: Outcomes Of Export Learning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior researchers have examined the improvement of experience and knowledge as a result of international business activities, particularly research studies conducted in international entrepreneurship studies such as Zahra et al (2000) and Fletcher and Harris (2012). The knowledge improvement includes international marketing knowledge, technical knowledge, as well as, internationalisation process know-how (Fletcher and Harris, 2012;Ibeh and Kasem, 2014;Zahra et al, 2000). For example, Ibeh and Kasem (2014) studied the impact of internationalisation adoption on the firms' acquisition of marketing learning.…”
Section: Non-financial Performancementioning
confidence: 99%
“…The knowledge improvement includes international marketing knowledge, technical knowledge, as well as, internationalisation process know-how (Fletcher and Harris, 2012;Ibeh and Kasem, 2014;Zahra et al, 2000). For example, Ibeh and Kasem (2014) studied the impact of internationalisation adoption on the firms' acquisition of marketing learning. They (ibid) found that firms' international business activities had positively influenced firms' acquisition of marketing knowledge.…”
Section: Non-financial Performancementioning
confidence: 99%